Pengaruh pengetahuan, pengalaman dan financial satisfaction terhadap keputusan investasi : Gender sebagai variabel moderasi - Febriansyah, Wivan; Purwidianti, Wida; Astuti, Herni Justiana; Utami, Restu Frida (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this research is to test gender where gender is used as a moderating variable to investigate the effect of knowledge, experience, and financial satisfaction on investment decision making. This research uses quantitative techniques. The data collection technique used was a survey using a questionnaire or questionnaire distributed online. The sample is 100 respondents who have made investment decisions and are domiciled in Banyumas and use a convenience sampling technique for the sample collected. Partial Least Square is the analytical technique used (PLS). The study results show that knowledge, experience, and financial satisfaction all have a significant effect on investment decisions. However, gender as a moderator element does not have a significant impact on the relationship.